Diagnosis and management of NSAID‐Exacerbated Respiratory Disease (N‐ERD)—a EAACI position paper - Kowalski, Marek L.; Agache, Ioana; Bavbek, Sevim; Bakirtas, Arzu; Blanca, Miguel; Bochenek, Grażyna; Bonini, Matteo; Heffler, Enrico; Klimek, Ludger; Laidlaw, Tanya M.; Mullol, Joaquim; Niżankowska‐Mogilnicka, Ewa; et al. (Allergy (Copenhagen), 2019)
NSAID‐exacerbated respiratory disease (N‐ERD) is a chronic eosinophilic, inflammatory disorder of the respiratory tract occurring in patients with asthma and/or chronic rhinosinusitis with nasal polyps (CRSwNP), symptoms of which are exacerbated by NSAIDs, including aspirin. Despite some progress in understanding of the pathophysiology of the syndrome, which affects 1/10 of patients with asthma and rhinosinusitis, it remains a diagnostic and therapeutic challenge. In order to provide evidence‐based recommendations for the diagnosis and management of N‐ERD, a panel of international experts was called by the EAACI Asthma Section. The document summarizes current knowledge on the pathophysiology and clinical presentation of N‐ERD pointing at significant heterogeneity of this syndrome. Critically evaluating the usefulness of diagnostic tools available, the paper offers practical algorithm for the diagnosis of N‐ERD. Recommendations for the most effective management of a patient with N‐ERD stressing the potential high morbidity and severity of the underlying asthma and rhinosinusitis are discussed and proposed. Newly described sub‐phenotypes and emerging sub‐endotypes of N‐ERD are potentially relevant for new and more specific (eg, biological) treatment modalities. Finally, the document defines major gaps in our knowledge on N‐ERD and unmet needs, which should be addressed in the future.